SMEs and environmental responsibility: a policy perspective. (5th March 2013) - Blundel, Richard; Monaghan, Adrian; Thomas, Christine
<x xml:space="preserve">Abstract</x> Environmental policies to promote environmentally sustainable economic activity have often concentrated on larger firms. However, increasing attention is being paid to the role of small‐ and medium‐sized enterprises (SMEs) and entrepreneurial actors. In this paper, we examine how policy tools are being used to improve the environmental performance of SMEs and to redirect entrepreneurial energies in more environmentally benign directions. The empirical section adopts a case‐based comparative method to examine four instances of policymaking, drawn from different countries and industry sectors. The paper argues that while some interventions have proved effective in their own terms, better integrated approaches are required to address today's complex and deep‐rooted sustainability challenges. The paper identifies several policy implications including the need to: clarify the purpose of any intervention, address potential interactions and trade‐offs; select appropriate tools based on informed reviews of the options; remain sensitive to context‐specific factors; and devise effective vehicles for the promotion and governance of entrepreneurial initiatives.